2003
DOI: 10.1038/sj.ijir.3900977
|View full text |Cite
|
Sign up to set email alerts
|

A journey through two lumens!

Abstract: This account describes studies from the Institute of Medical Physiology in the University of Copenhagen, starting in the mid 1970's, which included some of the earliest European laboratory investigations on human female genital function. The measurements involved vaginal pH, pO2, blood flow, motility, fluid and its ionic concentrations, amino-acid concentrations and electrical activity (transvaginal potential difference) usually in both the basal and sexual aroused states. The blood flow monitoring pioneered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The undergraduates in Animal Physiology spent two class sessions on sexual physiology, studying the mechanisms behind vaginal lubrication and penile erection (class reading: Levin, 2003), as well as the cardiopulmonary response to coitus (class reading: Fox and Fox, 1969). Students therefore had been introduced to and were able to describe the physiological mechanisms behind bodily changes correlating with lust or sexual activity, but the students had to rely on experience and perhaps imagination regarding the bodily signals of romance and stable pair-bonding.…”
Section: Methodsmentioning
confidence: 99%
“…The undergraduates in Animal Physiology spent two class sessions on sexual physiology, studying the mechanisms behind vaginal lubrication and penile erection (class reading: Levin, 2003), as well as the cardiopulmonary response to coitus (class reading: Fox and Fox, 1969). Students therefore had been introduced to and were able to describe the physiological mechanisms behind bodily changes correlating with lust or sexual activity, but the students had to rely on experience and perhaps imagination regarding the bodily signals of romance and stable pair-bonding.…”
Section: Methodsmentioning
confidence: 99%
“…Sommer et al reported use of a device to indirectly measure vaginal and minor labial blood flow, however, this device was not novel except that they also applied an electrode to the labia; otherwise it was the same as that developed previously by Levin and Wagner (31). Transcutaneous pO2 was measured using 2 Clark oxygen electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…The authors commented that sexual excitement with its concomitant vaginal lubrication did not appreciably change the pH. The lack of change in pH was likely due to two factors: 1) the upper vagina is least responsive to the formation of transudates and 2) the electrode may have been at a site that showed little change (31). This study was only done in 2 couples and subsequent researchers have never followed up these investigations.…”
Section: Resultsmentioning
confidence: 99%
“…In 2005, the World Association for Sexology created in Rome in 1978 changed its name to the "World Association for Sexual Health" (WAS). In terms of medical approaches, the terms "sexual medicine" and "specialist in sexual medicine" are being used more frequently in reference to members of the International Society for Sexual Medicine (ISSM; Bancroft, 2005;Levin, 2003;Riley, 2007). 2 These recent developments lead us to believe that what was called "sexology" in the 20th century is becoming increasingly controversial and is threatened both from the outside-the social, medical, and political context-and from the inside, due to the intrinsic transformations of the field itself.…”
Section: Sexology: History and Political Contextmentioning
confidence: 99%